Deciphering Novel Transcriptional Regulators of Soybean Hypocotyl Elongation Based on Gene Co-expression Network Analysis - Shen, Zhikang; Chen, Min (Frontiers in Plant Science, 2022)
Hypocotyl elongation is the key step of soybean seed germination, as well an important symbol of seedling vitality, but the regulatory mechanisms remain largely elusive. To address the problem, bioinformatics approaches along with the weighted gene co-expression network analysis (WGCNA) were carried out to elucidate the regulatory networks and identify key regulators underlying soybean hypocotyl elongation at transcriptional level. Combining results from WGCNA, yeast one hybridization, and phenotypic analysis of transgenic plants, a cyan module significantly associated with hypocotyl elongation was discerned, from which two novel regulatory submodules were identified as key candidates underpinning soybean hypocotyl elongation by modulating auxin and light responsive signaling pathways. Taken together, our results constructed the regulatory network and identified novel transcriptional regulators of soybean hypocotyl elongation based on WGCNA, which provide new insights into the global regulatory basis of soybean hypocotyl elongation and offer potential targets for soybean improvement to acquire cultivars with well-tuned hypocotyl elongation and seed germination vigor.